Hubungan Ketahanan dan Kerawanan Pangan dengan Social Capital dan Food Choice Rumah Tangga di kelurahan Kutowinangun Lor, Kecamatan Tingkir, Kota Salatiga - Geovani, Devin; Renyoet, Brigitte Sarah; Tauho, Kristiani Desimina (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Food security at this national level has received attention because it has not yet reached the word "resilience", which is indicated by Indonesia still importing staple food from Vietnam. One of the provinces in Indonesia with the best level of resilience is Central Java province with 93%, but it does not guarantee the condition of overall food security at the household level because it has different access to food. Utilization of social capital can realize food security related to food access, making it easier for people to choose food (food choice).Objectives: This study aims to examine the relationship between food security and insecurity with social capital and household food choice in the Kutowinangun Lor Village, Tingkir District, Salatiga City.Methods: The method used is a descriptive quantitative method. The statistical test used is the Chi Square test.Results: As many as 48.4% of respondents fall into the category of severe food insecurity. 54.8% of respondents do not actively participate in village organizations with moderate levels of social capital. 71% of respondents have a fairly good food choice. Bivariate analysis shows that there is no relationship between food security and social capital with a chi square test result of 0.709, while for food choice with food security, it shows that there is a relationship between the two with an iujiichi square result of 0.015.Conclusions: Most of the underprivileged households in Kutowinangun Lor fall into the category of severe food insecurity, with the result of a Chi Square test for social capital of i0.709. Meanwhile, the results of the Chi Square test on food choice are 0.015. Thus, food choice is the variable that most influences food security and insecurity in underprivileged households in Kutowinangun Lor.